(untitled) (Delta Medical College Journal, 2014)
Background: Age related cataract is the leading cause of blindness and visual impairment throughout the world. With the advent of microsurgical facilities simple cataract extraction surgery has been replaced by small incision cataract surgery (SICS) with posterior chamber intra ocular lens implant, which can be done either with clear corneal incision or scleral incision. Objective: To compare the post operative visual outcome in these two procedures of cataract surgery. Materials and method: This comparative study was carried out in the department of Ophthalmology, Delta Medical College & Hospital, Dhaka, Bangladesh, during the period of January 2010 to December 2012. Total 60 subjects indicated for age related cataract surgery irrespective of sex with the age range of 40-80 years with predefined inclusion and exclusion criteria were enrolled in the study. Subjects were randomly and equally distributed in 2 groups; Group A for SICS with clear corneal incision and group B for SICS with scleral incision. Post operative visual out come was evaluated by determining visual acuity and astigmatism in different occasions and was compared between groups. Statistical analysis was done by SPSS for windows version12. Results: The highest age incidence (43.3%) was found between 61 to 70 years of age group. Among study subjects 40 were male and 20 were female. Preoperative visual acuity and astigmatism were evenly distributed between groups. Regarding postoperative unaided visual outcome, 6/12 or better visual acuity was found in 19.98% cases in group A and 39.6% cases in group B at 1st week. At 6th week 6/6 vision was found in 36.3% in Group A and 56.1% in Group B and 46.2% in group A and 66% in group B without and with correction respectively. With refractive correction, 6/6 vision was attained in 60% subjects of group A and 86.67% of group B at 8th week. Post operative visual acuity was statistically significant in all occasions. Postoperative astigmatism of >0.50D was in 82.5% subjects of group A and 52.8% subjects of group B at 1st week. At 6th week postoperative astigmatism of less than 1D was in 79.95% subjects of Group A and 83.34% subjects of Group B. About 20% subjects in Group A and only 3.3% in Group B showed astigmatism of more than 1D and these differences on both the occasions were statistically significant. Conclusion: The post operative visual outcome was better in SICS with scleral incision (group B) than in SICS with clear corneal incision (Group-A). DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17793 Delta Med Col J. Jan 2014; 2(1): 22-27